(untitled) (International Journal of Biomedical Research, 2016)
Objectives: This study aims to detect the distribution of Blood groups in students attending Karpagam educational institutions. Also we aim to identify the cardiovascular and diabetic risk among them based on blood groups and demography. Methods : 977 students aged 17-20 years from various districts of Tamilnadu and Palakkad district of Kerala studying in Karpagam Educational institutions were taken for study in our Hospital in September 2013. Their Blood was collected in fasting state and analyzed for Blood grouping and Rh typing, Fasting Blood Sugar, Total Cholesterol, Triglycerides(TG), Low density lipoprotein (LDL), High Density Lipoprotein (HDL) and Very low density lipoprotein(VLDL). Results: Out of 977 students, 658 are males and 319 are females. The Blood group distributions are O-37.6%, B-31%, A-23.1% and AB-8.2%. Males had higher VLDL (pB>A>AB in the study population. Our study shows that A Positive population has higher risk of Coronary heart Disease (CVD) among blood groups. Also we found that students from palakkad district of kerala are having poor lipid levels and more prone for future coronary artery disease.